Gulag - Flannery, Sean (New York : Charter Books, 1987)
"KGB Colonel Rotislav Okulov was dead. Shot by his own agents as he tried to pass a Soviet secret to the Americans. CIA operative Tony Bertonelli was the only man who knew what Okulov revealed with his dying breath. Now, the KGB stalks Bertonelli from the streets of Moscow to the killing fields of Siberia--to keep the truth from the world at any cost."--Cover.
National College of Business and Arts
Keywords: Officials and employees -- Fiction; Suspense fiction